Penerapan model pembelajaran kooperatif tipe kancing gemerincing untuk meningkatkan keterampilan komunikasi dalam materi interaksi manusia dengan lingkungan pada kelas V sekolah dasar - Putri Yuli Alifah; Hasan Mahfud; Hadiyah Hadiyah (Universitas Sebelas Maret, 2020)
This study uses classroom action research aimed at improving communication skill by applying the talking chips type cooperative learning model in social studies. The subjects of the research were students of class V of SD Negeri Mangkuyudan No. 02 school year 2019/2020, totalling 30 students. Data collection techniques used were interviews, observation and documentation. Analysis of the data using the Miles and Huberman models. The results showed in the first cycle the persentage of students reached 54.5%. students. The results increased in cycle II to 73.5% students. From the research data, it shows that communication skill for students in grade V of Mangkuyudan Elementary School No. 02 increased. The improvement of communication skills after the application of the talking chips type cooperative learning model in social studies.Contribution of this research as knowledge in future research. Talking chips are expected to create fun learning for students.